2003
DOI: 10.1136/ijgc-00009577-200311000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Significance of microvascular density (MVD) in cervical cancer recurrence

Abstract: The purpose of this retrospective study of 118 patients with squamous cell cervical cancer from January 1990 to December 1993 was to evaluate angiogenesis as predictive factor of recurrence in cervical cancer stages II–III treated with standard radiotherapy. Microvessel density (MVD) was evaluated and correlated with other prognostic factors. MVD was greater than 20 in 67.8% of patients with recurrence (P = 0.002) in comparison to 39% of patients without. Disease-free survival was shorter in stage IIA and MVD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…[2] Tumor-associated endothelial cells secrete pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet-derived endothelial cell growth factor (PD-ECGF). [3] Plexin D1 was initially suggested to be a tumor marker, as it was found to be over expressed in brain tumours. [4] Plexin D1 was originally described as a receptor for the semaphorin Sema3E, [5] and it has been reported that semaphorins can effect migration and proliferation of some tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Tumor-associated endothelial cells secrete pro-angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet-derived endothelial cell growth factor (PD-ECGF). [3] Plexin D1 was initially suggested to be a tumor marker, as it was found to be over expressed in brain tumours. [4] Plexin D1 was originally described as a receptor for the semaphorin Sema3E, [5] and it has been reported that semaphorins can effect migration and proliferation of some tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies document the association between the MVD and ⁄ or the extent of endothelial proliferation, the pre-cancer and tumor stage, and the invasive disease of the cervical cancer. (3)(4)(5)(6) The expression of various angiogenesis stimulators, such as VEGFs, angiopoietins, and thymidine phosphorylase, has been reported in cervical cancer and dysplasia. (7,8) Several published reports similarly report stromal LVD in cervical neoplasia.…”
mentioning
confidence: 99%
“…Neoangiogenesis underlies solid tumor growth and malignant progression. For tumor tissue to proliferate and metastasize, neovascularization within it must have a certain phenotype before it can be achieved [ 19 ]. Quantitative analysis of microvessels in tumor tissues by immunohistochemical staining of vascular endothelial cell antigens accurately reflects the angiogenesis of tumor tissues [ 20 ], which is an important indicator for assessing whether tumor tissues were invasive, metastatic, recurrent for evaluating therapeutic efficacy, the results have been confirmed by a large number of studies.…”
Section: Discussionmentioning
confidence: 99%